Sb–Au-bearing chalcedonies in hot geothermal systems: insights from the jasperoids of Poggio Peloso (southern Tuscany, Italy). (16th April 2023) - Gliozzo, Elisabetta; Brogi, Andrea; Ruggieri, Giovanni; Langone, Antonio
Abstract: Detailed characterization was performed on the chalcedonies from the jasperoids of the Pietratonda–Poggio Peloso Sb–Au deposit (southern Tuscany, Italy). The main purpose was to retrieve information on the geothermal fluids that formed the chalcedonies and the source of antimony concentrations. Investigations were performed using optical microscopy, laser ablation inductively coupled plasma mass spectroscopy and X-ray diffraction on both the chalcedonies and the lithotypes cropping out in the area. The results obtained allow the chalcedonies of Pietratonda–Poggio Peloso to be described as a unicum, based on the very high contents of Sb that do not find a comparison in the literature. The textures showed multiple generations of silica that agree well with an environment characterized by multiple injections of mineralizing solutions, bearing variable physicochemical characteristics. The transport likely took place in an alkaline environment, while the acidification of the water may have favoured the precipitation at varying temperatures but not higher than 225 °C. The rocks from which the constituents may have been leached are the hosting carbonates and the surrounding metamorphic rocks. Among the examined rocks, the metamorphic rocks showed the most numerous and significant correspondences with the chalcedonies and were the only ones in which discrete amounts of gold contents were found.